2020
DOI: 10.1016/j.cub.2020.03.053
|View full text |Cite
|
Sign up to set email alerts
|

Natural Selection Shapes Variation in Genome-wide Recombination Rate in Drosophila pseudoobscura

Abstract: While recombination is widely recognized to be a key modulator of numerous evolutionary phenomena, we have a poor understanding of how recombination rate itself varies and evolves within a species. Here, we performed a comprehensive study of recombination rate (rate of meiotic crossing over) in two natural populations of Drosophila pseudoobscura from Utah and Arizona, USA. We used an amplicon sequencing approach to obtain high-quality genotypes in approximately 8000 individual backcrossed offspring (17 mapping… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 97 publications
(113 reference statements)
3
56
0
Order By: Relevance
“…Additionally, common FST -based approaches, including those used within this study can fail to detect other structural aspects of the genome that can be involved in adaptation (Wellenreuther et al, 2019), including copy number variation (Schrider et al, 2016;Nelson et al, 2019), local recombination rate variation (Reeve et al, 2016;Ortiz-Barrientos & James, 2017;Samuk et al, 2020), inversions (Kirkpatrick & Barton, 2006;Lowry & Willis, 2010;Faria et al, 2019), and transposons (González & Petrov, 2009;Schrader & Schmitz, 2019). Furthermore, the alleles contributing to adaptation are also difficult to detect if adaptation has proceeded by many alleles of small effect, which may be quite common in highly polygenic traits (Yeaman, 2015).…”
Section: The Effects Of Sampling On Parallelismmentioning
confidence: 99%
“…Additionally, common FST -based approaches, including those used within this study can fail to detect other structural aspects of the genome that can be involved in adaptation (Wellenreuther et al, 2019), including copy number variation (Schrider et al, 2016;Nelson et al, 2019), local recombination rate variation (Reeve et al, 2016;Ortiz-Barrientos & James, 2017;Samuk et al, 2020), inversions (Kirkpatrick & Barton, 2006;Lowry & Willis, 2010;Faria et al, 2019), and transposons (González & Petrov, 2009;Schrader & Schmitz, 2019). Furthermore, the alleles contributing to adaptation are also difficult to detect if adaptation has proceeded by many alleles of small effect, which may be quite common in highly polygenic traits (Yeaman, 2015).…”
Section: The Effects Of Sampling On Parallelismmentioning
confidence: 99%
“…Although studies investigating intra- and inter-specific recombination rate divergence are not uncommon (reviewed in Smukowski and Noor [2011] ), this kind of studies are usually deficient in an ecological understanding of the speciation process or lack the population-level sampling required for inferring the driving forces of recombination rate differentiation. However, a recent study examining two ecologically different populations of Drosophila pseudoobscura found that the divergence of genome-wide recombination rate is due to natural selection ( Samuk et al. 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another challenge in understanding the relationship between ecological shifts, directional selection, and recombination rate evolution is that multipopulation data on recombination rate is largely lacking (but see Saleem et al. 2001 and Samuk et al. 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Variation in recombination rate is likely to arise across taxa with variation in genome size and chromosome number (Stapley et al, 2017); in addition, the evolutionary costs and benefits of recombination may vary depending on the selective context, again leading to the expectation of recombination rate variation within and between populations (Otto and Barton, 2001;Otto and Lenormand, 2002). Indeed, cytogenetic and linkage mapping studies have shown that recombination rates can vary by orders of magnitude within and between chromosomes (Myers et al, 2005), individuals (Kong et al, 2004), populations (Samuk et al, 2020), sexes (Lenormand and Dutheil, 2005) and species (Stapley et al, 2017).…”
Section: Introductionmentioning
confidence: 99%